Future of Bangladeshi garments sizing system: Review - Haque Nizam Eanamul (Tekstilna industrija)
The Bangladeshi garment industry, a leading global exporter, faces significant challenges with sizing standards, largely due to its reliance on Western size charts that fail to accommodate the diverse body types of non-Western consumers. This research reviews the need for a localized sizing system informed by anthropometric data specific to Bangladesh. Current sizing practices, adapted from Western standards, often lead to high return rates, customer dissatisfaction, and financial and environmental costs due to wasted resources. Anthropometric studies, widely utilized in other Asian markets, have shown potential for creating regionally adaptable sizing systems; however, Bangladesh lacks a comprehensive, population-specific database of body measurements. The study highlights recent advancements in 3D body scanning and AI-driven predictive sizing models, which can offer precise measurements and accommodate diverse body types. Nonetheless, adoption remains limited due to technological and financial barriers. Furthermore, collaboration between industry stakeholders and academic institutions is necessary to address the gap in demographic and regional data, facilitating the development of an inclusive and accurate sizing system. This review underscores the potential benefits of a customized sizing framework for Bangladesh's garment industry, including reduced return rates, improved consumer satisfaction, and sustainability gains. By investing in anthropometric research and advanced technologies, Bangladesh could establish a pioneering, adaptive sizing standard that enhances the industry's global competitiveness while fostering size inclusivity and sustainability. The findings advocate for a coordinated approach to creating a comprehensive anthropometric database to better serve both local and international markets.